Eficacia del cuidado de enfermería en pacientes con insuficiencia renal crónica de la Unidad de Diálisis del IESS-Hospital General Machala octubre 2018-abril 2019 - Herrera Herrera, Wilma Beatriz (2019)
Nursing care in patients with chronic renal failure are activities that require a personal and professional value aimed at the conservation, restoration and self-care of life that is based on the nurse-patient therapeutic relationship; The purpose of this research was to determine the efficacy of nursing care in patients with chronic renal failure treated in the Dialysis Unit of the IESS-Machala General Hospital period from October 2018 to April 2019. This study was of a descriptive and cut type. transversal, with a universe of 14 nursing professionals working in the unit, and 72 patients. the instruments used for the data collection were the survey and observation, the results obtained were processed in the SPSS program, reaching the conclusion that the majority of surveyed users were male whose age ranged from 51 to 60 years, prevailing of married patients, with full secondary education, workers and general insurance. Regarding the level of compliance with biosafety regulations by nursing personnel, 72.2% do not comply with them, which constitutes a risk factor for staff and users. On the other hand, 93.1% of patients report that the effectiveness of care is low Keywords: Biosecurity rules, Restoration, Self-care.